Kajian Terhadap Standar Dan Sistem Sertifikasi Halal Yang Efektif Untuk Meningkatkan Daya Saing Usaha Di Pondok Pesantren Mambaus Sholihin - Mohammad Majduddin (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
This study aims to analyze the effectiveness of Halal Certification System (SSH) in supporting the growth of micro, small and medium enterprises (UMKM) in the Mambaus Sholihin Islamic Boarding School area. The method used in this research is descriptive qualitative by collecting data through interviews, observation, and documentation. The results of the study show that the implementation of SSH has had a positive impact on the growth of UMKM, especially in terms of increasing sales, developing new products, and increasing consumer confidence in the products being sold. In addition, SSH also assists UMKM in increasing the efficiency and effectiveness of the company's operations and fulfilling the halal standards set by the relevant halal certification bodies. However, there are several obstacles faced by UMKM in implementing SSH, such as limited human resources and high costs for halal certification. Therefore, support from the government and halal certification institutions is needed so that UMKM can more easily implement SSH and increase their business competitiveness in the market.